One Size Does Not Fit All: A Response to Institutionalizing Inequity - Edward Garcia Fierros (Disability Studies Quarterly, 2006)
In addition to providing a definition for ableism, Fierros addresses the main arguments in Gregg D. Beratan's article entitled, "Institutionalizing Inequity: Ableism, Racism, and IDEA, 2004". Specifically, Fierros presents competing ideas about the appropriateness of inclusion for students with special needs, discusses the notion of the Least Restrictive Environment (LRE) clause as ableist, provides data on the disproportionality of students with special needs, and examines the links between race and ableism. In terms of theory, he suggests that teacher preparation programs educate professionals about institutional ableism and racism. In terms of practice, he urges the use of differentiated instruction to support all students in inclusive settings.
Keywords: Disability Studies; Policy